2005
DOI: 10.3168/jds.s0022-0302(05)72914-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Carprofen Treatment Following Experimentally Induced Escherichia coli Mastitis in Primiparous Cows

Abstract: Acute Escherichia coli mastitis is one of the major sources of economic loss in the dairy industry due to reduced milk production, treatment costs, discarded milk, and occasional fatal disease. Nonsteroidal antiinflammatory drugs (NSAIDs) are frequently used as adjunctive therapy to antibiotics. The objective of the current study was to evaluate the effect of carprofen treatment following infusion of Escherichia coli into the mammary glands of primiparous cows during the periparturient period. Severity of mast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
46
1
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 39 publications
(52 reference statements)
5
46
1
1
Order By: Relevance
“…Pharmacological strategies to reduce the production of inftammatory mediators produced via the cyclooxygenase and lipoxygenase pathways have been studied extensively (Burvenich and Peeters, 1982;Anderson et al, 1986;Burvenich et al, 1989;Lohuis et al, 1989Lohuis et al, , 1991Rose et al, 1991;DeGraves and Anderson, 1993;Shpigel et al, 1994;Vangroenweghe et al, 2005;Banting et al, 2008). In those studies, pharmacological doses of nonsteroidal antiinftammatory dmgs were given either before the inftammatory challenge or at the onset of clinical signs of disease.…”
Section: Attenuating Inflammatory Responsesmentioning
confidence: 99%
“…Pharmacological strategies to reduce the production of inftammatory mediators produced via the cyclooxygenase and lipoxygenase pathways have been studied extensively (Burvenich and Peeters, 1982;Anderson et al, 1986;Burvenich et al, 1989;Lohuis et al, 1989Lohuis et al, , 1991Rose et al, 1991;DeGraves and Anderson, 1993;Shpigel et al, 1994;Vangroenweghe et al, 2005;Banting et al, 2008). In those studies, pharmacological doses of nonsteroidal antiinftammatory dmgs were given either before the inftammatory challenge or at the onset of clinical signs of disease.…”
Section: Attenuating Inflammatory Responsesmentioning
confidence: 99%
“…One intriguing finding was that meloxicam treatment during mastitis decreased the risk of removal from the herd by 58% in the 45 wk following treatment (McDougall et al, 2009). Carprofen was shown to partially alleviate the decrease in ruminal contractions during mastitis (Vangroenweghe et al, 2005), which could help prevent a subsequent displaced abomasum. Similarly, meloxicam administration 1 d after assisted calving increased time spent eating in the subsequent 24 h (Newby et al, 2013).…”
mentioning
confidence: 97%
“…Similar to the results from the caudal vena cava, PGE 2 concentration was increased by TNF and IL-1a infusions. Pezeshki et al [10] and Vangroenweghe et al [42] suggested that PGE 2 concentration in milk increased after intramammary challenge of E coli, and this PG production was related to bacterial growth and level of inflammatory response. Considering PGFM, all examined factors promoted its secretion, with exception of IL-1a.…”
Section: Plasma Samples Collected From the Milk Veinmentioning
confidence: 98%